2019
DOI: 10.4162/nrp.2019.13.3.256
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the dietary reference intakes for determining energy requirements in older adults

Abstract: BACKGROUND/OBJECTIVES The objectives of this study were to evaluate the accuracy of the Dietary Reference Intakes (DRI) for estimating the energy requirements of older adults, and to develop and validate new equations for predicting the energy requirements of this population group. MATERIALS/METHODS The study subjects were 25 men and 23 women with a mean age of 72.2 ± 3.9 years and 70.0 ± 3.3 years, and mean BMI of 24.0 ± 2.1 and 23.9 ± 2.7, respectively. The total ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In our study, these equations estimated higher REE values when compared to the values measured by IC, overestimating in men and women by 14.0 and 7.8% respectively. In a recent study carried out with the elderly, this equation had a bias of − 7.2% in men and − 6.6% in women [46]. Other study she was reported as accurate to estimate REE in men and women [47,48].…”
Section: Discussionmentioning
confidence: 92%
“…In our study, these equations estimated higher REE values when compared to the values measured by IC, overestimating in men and women by 14.0 and 7.8% respectively. In a recent study carried out with the elderly, this equation had a bias of − 7.2% in men and − 6.6% in women [46]. Other study she was reported as accurate to estimate REE in men and women [47,48].…”
Section: Discussionmentioning
confidence: 92%
“…In our study, these equations estimated higher REE values when compared to the values measured by IC, overestimating in men and women by 14.0% and 7.8% respectively. In a recent study carried out with the elderly, this equation had a bias of -7.2% in men and − 6.6% in women [46]. Other study she was reported as accurate to estimate REE in men and women [47,48].…”
Section: Discussionmentioning
confidence: 98%
“…Validation parameters included ‘mean % difference’ and ‘prediction % (accurate, underestimation, and overestimation)’. The mean % difference was calculated by the equations [EER(IOM) − TEE(DLW)]/TEE(DLW) × 100; ‘accurate prediction’ indicates the percentage of subjects predicted by the EER(IOM) equations within 90 and 110% TEE(DLW), ‘over-prediction %’ represents the percentage of subjects predicted by the EER(IOM) equations > 110% of TEE(DLW), and ‘under-prediction %’ explains the percentage of subjects predicted by the EER(IOM) equations < 90% of TEE(DLW) [ 3 5 6 11 ].…”
Section: Exploring For Articles That Validate the Eer(iom) Equations ...mentioning
confidence: 99%
“…Table 1 summarizes the basic characteristics and main outcomes of the 8 out of 11 papers reviewed that validated the EER(IOM) equations for EER based on TEE(DLW) [ 3 4 5 6 7 8 9 10 11 12 13 ]; 3 studies were performed in children (USA 1, Korea 2), 1 in adolescents (Portugal), 2 in adults (Korean), and 2 in the elderly (Korea and USA).…”
Section: Researches Validating the Eer(iom) Equations For Eer Based O...mentioning
confidence: 99%
See 1 more Smart Citation